Guaíra : a cidade em tempos de ditadura civil-militar (1964-1985) - Silva, Mara Dhulle dos Santos (2016)
The paper proposes the analysis of the experience of the city of Guaíra - PR in the context of Dictatorship of National Security, and its introduction in the years 1964-1985 in Brazil, that is, look at how this small town, located in the extreme west of Paraná, was affected by the dictates of the Dictatorship. We look at how the city was structured before the installation of the dictatorship; the importance of the national executive union with the municipal executive to direct the city project during the years of dictatorship; following also as some of these actions change local politics, and daily life of the city and its citizens today. Moreover, as will be discussed during the dictatorship period were applied different forms of coercion in this city of Paraná Western region, which makes the border with Mato Grosso do Sul State and the neighboring country of Paraguay